TREM2‐induced activation of microglia contributes to synaptic integrity in cognitively intact aged individuals with Alzheimer's neuropathology. (11th July 2022) - Fracassi, Anna; Marcatti, Michela; Tumurbaatar, Batbayar; Woltjer, Randall; Moreno, Sandra; Taglialatela, Giulio
Abstract: The existence of individuals who remain cognitively intact despite presenting histopathological signs of Alzheimer's disease (AD), here referred to as "Nondemented with AD neuropathology" (NDAN), suggests that some mechanisms are triggered to resist cognitive impairment. Exposed phosphatidylserine (ePS) represents a neuronal "eat‐me" signal involved in microglial‐mediated phagocytosis of damaged synapses. A possible mediator of this process is TREM2, a microglial surface receptor activated by ligands including PS. Based on TREM2 role in the scavenging function of microglia, we hypothesize that an efficient microglial phagocytosis of damaged synapses underlies synaptic resilience in NDAN, thus protecting from memory deficits. Using immunofluorescence microscopy, we performed a comparative study of human post‐mortem frontal cortices of aged‐matched, AD and NDAN individuals. We studied the distribution of activated microglia (IBA1, IBA1 + /CD68 + cells) and phagocytic microglia‐related proteins (TREM2, DAP12), demonstrating higher microglial activation and TREM2 expression in NDAN versus AD. A study of the preservation of synapses around plaques, assessed using MAP2 and βIII tubulin as dendritic and axonal markers, respectively, and PSD95 as a postsynaptic marker, revealed preserved axonal/dendritic structure around plaques in NDAN versus AD. Moreover, high levels of PSD95 around NDAN plaques and the colocalization of PSD95 with CD68 indicated a prompt removal of damaged synapses by phagocytic microglia. Furthermore, Annexin V assay on aged‐matched, AD and NDAN individuals synaptosomes revealed increased levels of ePS in NDAN, confirming damaged synapses engulfment. Our results suggest a higher efficiency of TREM2‐induced phagocytic microglia in removing damaged synapses, underlying synaptic resilience in NDAN individuals. Abstract : Efficient TREM2‐phagocytic microglia underlie synaptic resilience in NDAN, removing damaged synpases, contributing to synaptic integrity and protecting from memory deficits.